Serial and parallel reliability models for robot arm reliability analysis. (August 2020) - Li, Songhao; Xu, Chen; Wang, Yawen; Xie, Liyang
Abstract: For reliability evaluation of a robot arm designed for tunnel boring machine, a serial system reliability model for arm strength and a summation (cumulative deformation) system reliability model for the fingers of the robot arm are developed. To reflect the effect of load uncertainty, total probability theorem is applied to develop mult-layer, multi-variate reliability models. With the total probability theorem and the multi-layer configuration of the reliability models, such models reflect the effect of load intensity uncertainty, load action number uncertainty, load peak distribution uncertainty, and component strength uncertainty hierarchically.